The health and safety of being fishermen: A literature review - Alayyannur, Putri Ayuni; Ramdhan, Doni Hikmat; Tejamaya, Mila (Journal of the Pakistan Medical Association, 2023)
Objective: To explore the occupational safety and health of fishermen in coastal areas, and the causes and health problems experienced by them. Method: The systematic review was conducted in February 2021, and comprised search on Google Cendekia, ScienceDirect, ProQuest, PubMed and BioMed Central databases for relevant studies published in English or Indonesian from 2016 to February 2021. The key words used were fisheries, fishermen, occupational, safety and health. The studies identified were assessed using population-intervention-control-outcomes-study framework. Results: Of the 24,271 studies initially identified, 23(0.09%) were reviewed in detail. Findings showed that fishing accidents occurred every year, causing traumatic injuries. The cause of such accidents had both internal and external factors. Health problems experienced by the fishermen included physical and mental health disorders. Conclusion: The occupational safety and health of fishermen need to be paid attention to. Keywords: Global warming, Temperature, Occupational health, Accidental falls, Hunting, Mental health.